The activities of the LAMBDA (Laboratory of Milano Bicocca university for Dating and Archaeometry): what's new?. Issue 1 (1st April 2022) - Panzeri, L; Galli, A.; Maspero, F; Saleh, M; Martini, M
Abstract: The LAMBDA, Laboratory of Milano Bicocca University for Dating and Archaeometry, has a forty-years experience started with the first thermoluminescence dating activities in Italy in the early eighties. Soon after, other dating techniques (Optically Stimulated Luminescence, OSL, Radiocarbon, Dendrochronology and recently Rehydroxylation) have been studied and dedicated laboratories have been set up, where the physical basis of the techniques are constantly under investigation, mainly for what concerns the role of defects in quartz in the luminescence processes. LAMBDA covers other prominent archaeometry fields such as dating of mortars by OSL and Radiocarbon, surface dating of bricks and rehydroxylation dating. In this paper we will present the recent results in dating field focusing on mortar and surface dating. Furthermore, the results of a recent dating campaign to rediscover ancient Milan will be presented.